ANALYSIS OF CASH WAQF IN INDONESIA IN SUPPORTING SUSTAINEBLE DEVELOPMENT GOALS (SDGs) - Robi Gunawan; Muhammad Fajri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The economy in Indonesia since the pandemic storm in 2019 has experienced various shocks, many large companies have been forced to lay off dozens or even hundreds of employees due to the declining economic graph. The impact is in the form of poverty and even economic difficulties that are increasingly visible. This is a big challenge for Indonesia in its efforts to survive and continue to try to improve the economy through strategic programs with the aim of reducing the decline in society after the pandemic, educating the public to prepare themselves to help grow the Indonesian economy with MSMEs. The Indonesian Waqf Board wants to join hands with the government in helping to improve the economy so that it gets better, namely by optimizing the management of waqf money. This big program requires many parties to take part in it, for example the Ministry of Religion has participated in campaigning for the optimization of waqf money through its institutions. Because waqf money when viewed from long-term progress is able to welcome and support the Sustainable Development Goals (SDGs) initiated by the United Nations with the goal of sustainable development. So that in the future Indonesia will be able to become a country that is advanced in the economic sector.